If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -36 = 4(x + 1) Reorder the terms: -36 = 4(1 + x) -36 = (1 * 4 + x * 4) -36 = (4 + 4x) Solving -36 = 4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -36 + -4x = 4 + 4x + -4x Combine like terms: 4x + -4x = 0 -36 + -4x = 4 + 0 -36 + -4x = 4 Add '36' to each side of the equation. -36 + 36 + -4x = 4 + 36 Combine like terms: -36 + 36 = 0 0 + -4x = 4 + 36 -4x = 4 + 36 Combine like terms: 4 + 36 = 40 -4x = 40 Divide each side by '-4'. x = -10 Simplifying x = -10
| -9x+18=-6x+27 | | x+e=1 | | 8p=18 | | -40x-20=12x+24 | | 2(5x+4)-1=4x-23 | | w^2(3w-1)+(3w-1)=0 | | -27=3(x-4) | | 7x(-5)= | | x^4=2x^3+8x^2 | | 3.82+1.25x=5.9 | | 3(-n-1)=-16n+49 | | 2X+15=20+3 | | x^2-8x-13=2x+3 | | 8(x+1)+5(x+7)=56 | | 0.6d+6=66 | | -4x-15=-9 | | xc=92 | | 139-7x=20x+16 | | v^2+5v-36= | | x^2-4x+8=5 | | 42+5c=9c-6 | | cx=92 | | 24=-3(x-2)+2 | | -3+5x=13 | | 56-2m=6m | | 300+(-85)= | | v^2+3v+2= | | 7x+10=10x | | 9x-1=1.4(12x+68) | | 3m-7=34 | | 5x=k | | x^4=6x^3+16x^2 |